Tipologi Bangunan di Jalan Pakubowono Kebayoran Baru, Jakarta Selatan - Mariana, Yosica (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Façade is the front of the building which is facing the street. It is one of the architectural elements of the city that can? speak out? the meaning of the building. In addition, façade is also a part of urban environment order which needs to be sustainable. The transformation of building function often impacts on changes in the composition of façade. Therefore, it is very interesting to be observed, especially along Pakubowono's street, which has distinctively Jengki architectural buildings. The purpose of this study is to explore the the extent of architectural transformation that occurs in Jengki style building by using descriptive methods. The result showed that Pakubowono area has undergone a change and assimilation of forms, although it is not very significant in the building typology. There are many changes that occur in materials and building elements which is an attempt to maintain its damaged parts.